3 - Economie souterraine, Endettement et Finances publiques à Madagascar: by Olivier Raninhat - Olivier Raninhat, (Africa Development, 1988)
The relation between the underground economy (the informal sector) debt and public finance poses interesting political and economic questions. In Madagascar as well as in many developing countries, growing fiscal crisis and the increase in public debt and the attendant severe impact on society are the major characteristics of public finance. The regression of the production system results in the enlargement of sectors of distribution as the arena for accumulation of wealth develops into parallel channels to the official sector which is faced with scarcity of supply. In this context the economic base of the state ...which is largely based on foreign trade tends to shrink. The volume of the underground economy and the importance of its activities are related to the weight, area of application of the fiscal system as well as the extent of control and regulation of economic activity. The shortage of state revenues, namely because of loss of opportunities resulting from the underground economy transforms the deficit into a structural one. Thus, the under ground economy constitutes one of the counterparts of debt. The underground economy stands for the cost of reproduction of the productive system. In the dynamics of the relation of forces which prevails between the underground economy and the official economy which, although weakened, is largely supported by the out side world, the underground economy becomes a condition necessary for the functionning of the internal logic of the system. It also ensures the development of self centered industry.